Preliminary investigations of hydrogen peroxide treatment of selected ornamental fishes and efficacy against external bacteria and parasites in green swordtails - Russo, Riccardo (Journal of aquatic animal health, 2007)
The objectives of these preliminary studies were to evaluate the use of hydrogen peroxide (H2O2) for the treatment of selected species of ornamental fishes and its efficacy in treating external bacteria and parasites. In the first part of the study, fish of five species (serpae tetra Hyphessobrycon eques (also known as Serpa tetra H. serpae), tiger barb Puntius tetrazona, blue gourami Trichogaster trichopterus, suckermouth catfish Hypostomus plecostomus, and green swordtail Xiphophorus hellerii) were exposed to H2O2 for 1 h at concentrations between 6 and 34 mg/L or for 24 h at concentrations between 1 and 6 mg/L. The results were species specific: green swordtails tolerated all of the treatments, serpae tetras and tiger barbs were sensitive only to the highest concentration, and mortalities of suckermouth catfish and blue gourami were recorded in every treatment. In the second part of the study, clinically healthy green swordtails and fish infested with external motile rod-shaped bacteria (i.e., Ichthyobodo spp., Trichodina spp., and Gyrodactylus spp.) were treated with several concentrations of H2O2. A single H2O2 treatment of 3.1 mg/L or more for 1 h effectively eliminated external bacteria, concentrations of 6.5 mg/L or more appeared to effectively kill Ichthyobodo spp., and none of the treatments tested was effective against Trichodina spp. or Gyrodactylus spp. These preliminary findings suggest that H2O2 is effective for treating certain external bacterial infections and flagellate infestations in some species of ornamental fish at the dosages tested. Other treatment regimens may need to be tested for effectiveness against Trichodina spp. and Dactylogyrus spp